"SOCIETAL PERSPECTIVES ON THE STIGMATIZATION OF THE REGGAE MUSIC SCENE AS ASSOCIATED WITH CANNABIS USE" - Adam Fauzan Rivaldi; Nadia Intan Fadila (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine public perceptions of the reggae music scene, which is often stigmatized as being closely associated with marijuana use. Such stigmatization is shaped by various social, cultural, and media factors that reinforce the association between reggae music, Rastafarian lifestyle, and cannabis consumption. Using a descriptive qualitative approach and labeling theory as the analytical framework, this research involved three categories of informants: reggae musicians, reggae listeners, and members of the general public. The findings indicate that negative public perceptions of the reggae scene are influenced by prevailing stereotypes and certain social experiences, such as the discovery of marijuana remnants after reggae concerts. However, some segments of the public recognize that not all individuals involved in the reggae scene are marijuana users and consider such stigmas to be unfair generalizations. The study concludes that the stigma surrounding the reggae scene is a result of social constructions imposed by dominant groups and has led to limited space for expression and reduced social acceptance of reggae culture practitioners.Keywords: stigma, reggae music, marijuana, public perception, labeling theoryINTRODUCTIONMusic is a medium or form of art that evolves in tandem with the progression of time. The development of music has always aligned with the advancement of human civilization. Therefore, music cannot be separated from human life (Soedarsono, 1992). As life and times continue to evolve, numerous new music genres have emergedeach developing rapidly, characterized by unique features, and influencing various aspects of global life. One particular genre that has attracted significant public attention is reggae music. This genre originated in Jamaica and first emerged in the late 1960s (Pratama, 2021).The rise in popularity of reggae music, especially among Indonesian musicians, has given birth to a new style that characterizes the genre. Reggae is commonly associated with dreadlocksknown in Indonesia as rambut gimbalas well as the red, yellow, and green flag, and the use of marijuana. These characteristics were popularized by Bob Marley, who is considered a central figure and icon among reggae enthusiasts. The development and introduction of regae music in Indonesia began in the 1980s (Fadhil, 2016).Reggae music is often linked to the Rastafari movement, whose followers tend to live a minimalist, simple, and natural lifestyle. In Rastafarian belief, marijuana is viewed as a sacred plant with spiritual energy, often used to strengthen the connection with God, and not merely for recreational purpose. At its core, Rastafari is a spiritual movement that goes beyond religion—it is also a cultural force that influences music, society, politics, and many other aspectsof life (Muhammad, 2021).In the context of reggae culture, the use of marijuana is often viewed as a symbolic expression of freedom, a form of protest against restrictive norms, and an act of resistance against injustice. However, this form of rebellion is frequently misunderstoodand tends to generate negative stigma, especially in countries with strict regulations against narcotics(Waldstein, 2019). For instance, in Indonesia, individuals who dress in red, yellow, and green colors, wear dreadlocks, or simply enjoy listening to reggae music are often labeled by the general public as marijuana users. This has led to widespread misconceptions about reggae music and its cultural meaning (Pamungkas, 2018).The following are several reggae music practitioners who have been arrested by authorities over a period of time due to their involvement as marijuana users.